Faith and Place: An Essay in Embodied Religious Epistemology. By Mark R. Wynn - McGhee, Michael (The journal of theological studies, 2010)
This is an essay on knowledge of place and on the significance of place for our knowledge of God. It is intriguing and compelling and will contribute to a new philosophical theology that takes serious account of human embodiment and makes essential connection with aesthetics. The essay has the high merit of provoking thought and, no doubt, interesting disagreement. There are discussions here of the idea of the genius loci and that of God as genius mundi, the (brooding) sense of place and presence.